2019
DOI: 10.1016/j.soilbio.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial functions are affected by organic matter removal in temperate deciduous forest

Abstract: A growing demand for renewable carbon (C) has led to intensified forest management resulting in the use of forest residues (e.g. canopy, bark or litter layer) as energy sources with potential modifications of soil properties and tree productivity. Because microbes mediate the recycling of C and nutrients sequestered in organic matter, we investigated the effects of organic matter (OM) removal on soil properties, root surfaces, microbial functions and abundance using a new observational forest network. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 74 publications
(80 reference statements)
0
10
1
Order By: Relevance
“…With the development of molecular biology technology, scholars have expanded the focus of attention from soil microbial community composition to functional prediction. Studies have indicated that soil microbial function are closely related to the quantity of plant detritus input into soil ( Maillard et al, 2019 ; Wang et al, 2020b ; Feng et al, 2022 ). For example, Wang et al (2019) suggested that litter addition can increase the functional groups associated with soil microbial C metabolism, while NL has a negative effect on microbial functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of molecular biology technology, scholars have expanded the focus of attention from soil microbial community composition to functional prediction. Studies have indicated that soil microbial function are closely related to the quantity of plant detritus input into soil ( Maillard et al, 2019 ; Wang et al, 2020b ; Feng et al, 2022 ). For example, Wang et al (2019) suggested that litter addition can increase the functional groups associated with soil microbial C metabolism, while NL has a negative effect on microbial functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 years of carrying out treatments in the same experimental plots as those used in our study, Maillard et al(2019), did not nd any change in the soil pH of the treatment plots, but the CEC of the soil was signi cantly decreased. At present, after 5 years, we have found a signi cant increase in the ratio of Al/Mg (p = 0.001) in the treatment plots (Fig.…”
Section: Nutrient Statusmentioning
confidence: 44%
“…Generically, soil fertility in the site Darney was comparatively poorer than site Champenoux (Akroume et al, 2016). To evaluate the treatment effect, i.e., RHRL on soil properties, a study was conducted by Maillard et al 2019 at site Darney in beech trees after 3 years of the establishment of experimental plots. The study found that, the total soil N, soil organic C, soil organic matter (SOM) and pH were not impacted by removing harvest residuals, but removing harvest residuals signi cantly affected the other soil parameters measured in the 0-5cm soil layer (Fig.…”
Section: Soil Informationmentioning
confidence: 99%
See 2 more Smart Citations